Diversity and Abundance of Soil Arthropods in Terrestrial Area of Situ Lengkong Panjalu, West Java, Indonesia - Bahana Aditya Adnan; Tiktiek Kurniawati; Manap Trianto (Jurnal Biodjati, 2024)
Soil arthropods play an important role in nutrient cycling and maintenance of soil structure. Thus, their abundance and diversity can indicate the biological quality of the soil. Due to different soil management practices, arthropods are also very sensitive to environmental changes. This study aims to analyze the abundance and diversity of soil arthropods and the environmental factors that support the abundance of soil arthropods in terrestrial of Situ Lengkong Panjalu, West Java, Indonesia. The methods used to obtain samples of soil arthropods are pitfall trap. Soil arthropod data were analyzed to determine the Shannon diversity index (H'), Margalef richness index (R), and Evenness index (E). The effect of abiotic environmental factors was analyzed using Principal Component Analysis (PCA). A total of 1263 arthropods were found in Situ Lengkong Panjalu, belonging to 11 orders, 24 families, and 32 morphospecies. The current work determined the scores of H'= 2.08, R = 3,08, and E = 0.72 of soil arthropods in Situ Lengkong Panjalu, West Java, Indonesia. Results revealed that humidity is one such environmental parameter affecting the presence of soil arthropods in Situ Lengkong Panjalu, West Java, Indonesia. This research can be used as a guide in validating and conservation of the habitat of soil arthropod species on West Java